Genetic variability, heritability, genetic advance and character association of Indian mustard (Brassica juncea L.) - Jagdish Prasad Chaurasiya; Mahak Singh; and Prakriti Tomar (Journal of Oilseed Brassica, 2026)
An investigation was undertaken to study the Genetic variability, heritability, genetic advance and character associationof Indian mustard (Brassica juncea L.) of twelve characters namely days to 50% flowering, days to maturity, plant height(cm), no. of primary branches per plant, no. of secondary branches per plant, no. of siliquae per plant, no. of seeds persiliqua ,1000- seed weight (g), biological yield per plant (g), harvest index (%), oil content (%) , seed yield per plant (g) inseven Indian mustard germplasm lines. The experiment material was evaluated in a randomized complete block designwith three replications. Analysis of variance estimates of all the characters were found highly significant. Coefficient ofvariation for GCV and PCV were found high for the following traits i.e. primary branches per plant, 1000- seed weight (g),no. of seeds per siliqua and seed yield per plant. All the characters showing higher heritability except biological yield perplant (g). no. of siliquae per plant show higher genetic advance. Correlation study revealed that that seed yield hadsignificant and positive association with no. of siliqua per plant (0.21G & 0.19P), number of Seeds per siliqua (0.35G &0.13P),1000 seed weight (0.52G&0.45P), harvest index (0.79G & 0.78P) biological yield (0.97G & 0.44P), no. of secondarybranches per plant (0.74G & 0.29P), number of primary branches (0.77G & 0.54P) and oil content (0.70G & 0.51P) atgenotypic and phenotypic levels.